2015
DOI: 10.1109/mvt.2015.2410341
|View full text |Cite
|
Sign up to set email alerts
|

Vehicular Communications: Survey and Challenges of Channel and Propagation Models

Abstract: Abstract-Vehicular communication is characterized by a dynamic environment, high mobility, and comparatively low antenna heights on the communicating entities (vehicles and roadside units). These characteristics make the vehicular propagation and channel modeling particularly challenging. In this survey paper, we classify and describe the most relevant vehicular propagation and channel models, with a particular focus on the usability of the models for the evaluation of protocols and applications. We first clas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
113
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(115 citation statements)
references
References 35 publications
(97 reference statements)
0
113
1
1
Order By: Relevance
“…Two recent surveys of these models are available in [2] and [3]. Given the number of scenarios, environments, and classification of models w.r.t.…”
Section: V2x Channel Measurements and Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent surveys of these models are available in [2] and [3]. Given the number of scenarios, environments, and classification of models w.r.t.…”
Section: V2x Channel Measurements and Modelingmentioning
confidence: 99%
“…However, up to now, 3GPP models in [4] do not implement some key V2X features, such as the impact of dual mobility on fast fading parameters (necessary for V2V), they do not consider V2X-specific scenarios (highway, streetlevel urban, roadside unit-to-Vehicle, V2V), and have not considered V2X-specific antennas. For further details, see [2], [3], [4].…”
Section: V2x Channel Measurements and Modelingmentioning
confidence: 99%
“…However these models are not efficient, since these models do not estimate effects of signal attenuation in presence of obstacle in Line of Sight (LOS) between transmitter and the receiver. In [21] showed that the presence of obstacle in LOS between transmitter and receiver affect the signal attenuation at the receiver. To address the addition attenuation requirement for effective transmission, here we model the obstacle in our modelling to evaluate the γ in Eq.(4).…”
Section: Adaptive Mac Schedular For Cev Enviroment Model For V2v In Vmentioning
confidence: 99%
“…The signal, also, may be scattering due to obstacles that found in the road between Tx and Rx and then reach the strong power to the receiver, so this path is NLOS. The receiver received signal with different amplitudes and times of arrival due to such multipath [3,4]. Radio wave may be propagated in all direction through sky mode and can travel through long distance.…”
Section: Introductionmentioning
confidence: 99%